Applicant reactions to interview focus : recruitment-focused interview, selection-focused interview and mixed-focused interview - Suhaina binti Sulaiman (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Effective recruitment practice can enhance an organization's ability to generate significant interest among applicants to apply for a job, maximize qualifications from the applicant pool and obtain top talent within that pool. These cannot be accomplished if organizations are perceived negatively by applicants. The present study examined applicant reactions to different interview focus by comparing between recruitment-focused, selection-focused, and mixed-focused interview i.e. recruitmentfocused interview followed by selection-focused interview. Forty-seven matriculation teachers participated in the present study which used repeated measures design as job applicants for foundation teacher position. The participants were given transcripts of foundation teacher employment interview questions to be read. The participants then responded to adapted Process Fairness Scale questionnaire and indicated their fairness perception on the recruitment-focused interview, selection-focused interview and mixed-focused interview questions in the transcript. The results for the one-way within-subjects ANOVA indicated a significant difference on applicant reaction to different interview focus in terms of its process fairness, F(2, 92) = 210.29, p < .001, multivariate η 2 = .82. Pairwise comparisons were also conducted among the means for perception fairness in the three types of interview focus and all the comparisons are significant with mean for selection-focused interview (M=13.47; SD= 1.40) significantly greater than the mean of recruitment-focused interview (M = 8.68; SD = 1.98), t (46) = -15.08; p <0.01; mean of mixed-focused interview (M = 14.45; SD = 1.21) greater than mean of selection-focused interview (M = 13.47; SD = 1.40), t (46) = -4.01; p <0.01; and mean of mixed-focused interview (M = 14.45; SD = 1.21) greater than mean of recruitment-focused interview (M = 8.68; SD = 1.98) and with t (46) = -17.29; p < 0.01. The findings of present research were discussed in relation to past literature, theoretical framework, limitations, implications and recommendations for future research.